Integrating Management, Education, and Islamic Thought: A Conceptual Framework for Holistic Institutional Development - Sutrisno; Zaheemath Jameel; Mohabeer (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2025)
This study addresses a critical gap in the field of educational management, namely the insufficient integration of Islamic ethical and spiritual principles into contemporary theories of management and educational practice. It proposes a conceptual and theoretical framework that bridges management, education, and Islamic thought to advance holistic institutional development. Employing a library-based descriptive–analytical methodology, the study critically synthesizes classical Islamic scholarship, including the works of al-Ghazālī and Ibn Khaldūn, with modern theories of management and education articulated by scholars such as Deming and Dewey, alongside global policy frameworks such as the United Nations Sustainable Development Goal 4. Conceptual triangulation across these intellectual traditions was used to enhance analytical depth and validate the findings. The results reveal three principal dimensions of integration: first, the convergence of management and education, which aligns strategic planning and continuous quality improvement with human development and social responsibility; second, the ethical and spiritual contributions of Islamic thought, which embed the principles of amanah (trust), ‘adl (justice), and shura (consultation) into leadership, governance, and curriculum design; and third, the broader interdisciplinary implications for cultivating institutional cultures grounded in values, participatory governance, and equity-oriented curricula. The study contributes theoretically by positioning Islamic ethics as foundational design parameters within educational management discourse and practically by offering actionable insights for institutional governance, leadership capacity-building, and curriculum reform. The proposed framework provides a pathway for institutions to achieve global competitiveness while remaining anchored in ethical authenticity and cultural integrity.